Pengaruh Stres Kerja Pegawai terhadap Pencapaian Tujuan Rumah Sakit - Salwa Febriana Ekasari Siregar; Canttika Canttika; Maritza Adelia Putri; Seftiani Syafira; Nadya Nur Syafina Putri; Nadhira Nasywa Cordellia; Amanda Safitri; Fanny Fadlilah; Tuanku Banang Rabbani Imsyaamru (Pratama Medika : Jurnal Kesehatan, 2026)
Work stress is one of the main challenges faced by hospital employees and has the potential to hinder the achievement of institutional goals. The high workload, shift work system, and psychological and physical pressure make health workers vulnerable to occupational stress. This study is a literature review of 11 scientific articles obtained from databases such as Google Scholar, Scopus, and PubMed with a publication year range of 2018 to 2025. The purpose of this study is to analyze the effect of work stress on the achievement of hospital goals. The results showed that job stress negatively impacts quality of work life, job satisfaction, motivation, organizational citizenship behavior, and individual performance. These impacts directly or indirectly affect the quality of service and the effectiveness of the hospital organization in achieving its goals. Therefore, comprehensive management of work stress is a strategic step in maintaining the well-being of health workers and supporting the achievement of hospital goals.